Burst Failure Characteristics and Energy Evolution Law of Coal with Prefabricated Cracks at Different Angles - Zhang, Xiufeng; Han, Yueyong; Chen, Yang; Ma, Xingyin; Zhang, Xinrong; Man, Cao; Yin, Yanchun (Shock and Vibration, 2024)
In order to study the influence of fissures on the burst tendency of coal, the test and numerical simulation of the burst tendency of coal with different burst angles were carried out. The evolution law of the burst tendency index of coal under the influence of burst angle was analyzed, and the mechanism of energy storage and release of coal under the influence of fissure angle was revealed. The results show that compared with the specimens without prefabricated cracks, the uniaxial compressive strength of the specimens with 0° cracks is reduced by 48.4%, the dynamic failure time is increased by 279.4%, the burst energy index is reduced by 54%, and the burst energy velocity index is reduced by 87.9%. After that, with the increase of prefabricated crack angle, the uniaxial compressive strength of coal increases gradually, the dynamic failure time decreases gradually, the burst energy index increases gradually, and the burst energy velocity index increases gradually. That is to say, the larger the crack angle contained in the coal body, the stronger the burst tendency of the coal body, but it is still lower than that of the complete coal body. With the increase of prefabricated crack angle, the proportion of prepeak elastic energy of coal body increases, the less energy dissipation in the whole loading process of coal body, and the faster energy release rate during failure. The research results can provide some theoretical support for the prevention and control of rock burst disaster.